INOVASI GURU DALAM MENGEMBANGKAN KONTEN EDUKASI PLATFORM YOUTUBE SEBAGAI MEDIA PEMBELAJARAN BIOLOGI - Qurrotul A’yuni; Fifin Naili Rizqi; Feby Aiyuni; Nazilatur Rahmah; Imron Fauzi (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2022)
The purpose of this study was to determine the concept of teacher innovation in developing educational content on the YouTube platform as a learning medium and to determine the form of educational content that can be used as a medium for learning biology. This study was designed using a qualitative method with the type of library research. The data analysis procedure was carried out by searching, collecting, and processing various valid sources such as printed books, e-books, and similar e-journals as article references. The result of this study is that teachers have a great opportunity to innovate and develop learning media in the develop learning media in the form of educational content on the YouTube platform in learning biology. The development of educational content is useful for increasing student interest in learning, making it easier for students to receive biology material, and providing opportunities for students to study wherever and whenever. Educational content can be in the form of learning videos, teaching videos, tutorial videos, and even animated videos. The conclusion of this study is that teachers can develop content in various forms freely as a medium for learning biology on the condition that the content contains information on biological knowledge.